2020
DOI: 10.3390/ma13112553
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Arsenic(V) Removal on an Iron-Based Sorbent Modified by Lanthanum(III)

Abstract: Modification of a commercial iron oxide ion exchanger (Arsen Xnp) was carried out to enhance the removal of arsenic(V) ions. The modification consisted of the adsorption of lanthanum(III) ions on the Arsen Xnp surface. After adsorption, the material was dried at 313 K to obtain the modified ion exchanger Arsen Xnp-La(III). The modification process itself was tested for optimal pH, kinetics, and equilibrium adsorption isotherm study. Accurate sorbent characteristics were made using, among others, SEM, FTIR, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…The findings of this research are consistent with the study of Dudek and Koodyska [68], who concluded that 120 min is an appropriate duration to achieve As removal equilibrium [68]. Attinti et al [69] also used silicon nanoparticles covered with goethite and achieved equilibrium at 120 min.…”
Section: Effect Of Contact Timesupporting
confidence: 89%
“…The findings of this research are consistent with the study of Dudek and Koodyska [68], who concluded that 120 min is an appropriate duration to achieve As removal equilibrium [68]. Attinti et al [69] also used silicon nanoparticles covered with goethite and achieved equilibrium at 120 min.…”
Section: Effect Of Contact Timesupporting
confidence: 89%
“…e FTIR spectra of QC-MC and QC-MT represent different functional groups of these materials. QC-MC and QC-MT PZC curves are similar to other studies [20][21][22]. erefore, the difference between acid and basic pH is very large for QC-MC and QC-MT.…”
Section: Point Of Charge Zerosupporting
confidence: 86%
“…Although the majority of the internal pores are mesopores according to IUPAC classification, they are called macroporous (in the case of Amberlites ion exchangers they are called macroreticular) [59]. Particularly, Dowex M 4195 is regarded as a material intermediate between the ion exchanger and the non-porous one that is with a not completely functionalized matrix [60][61][62][63][64]. As was mentioned in [63], such resin is characterized by a large operating capacity (higher regeneration efficiency), smaller leakage, and greater physical and chemical stability than the conventional and fully functionalized resins of the same particle size.…”
Section: Dowex M 4195mentioning
confidence: 99%